Electrochemical Sensor Platform for Rapid Detection of Foodborne Toxins - Kundan Kumar Mishra; Krupa M. Thakkar; Vikram Narayanan Dhamu; Sriram Muthukumar; Shalini Prasad (Biosensors, 2025)
Zearalenone (ZEA), a potent mycotoxin commonly found in contaminated grains, presents a serious threat to food safety and public health. Conventional detection methods, including culture-based assays and laboratory-bound analytical tools, are often time-consuming, require specialized infrastructure, and lack portability, limiting their utility for rapid, on-site screening. In response, this study introduces a compact, real-time electrochemical sensing platform for the swift and selective detection of ZEA in corn flour matrices. Utilizing a non-faradaic, label-free approach based on Electrochemical Impedance Spectroscopy (EIS), the sensor leverages ZEA-specific antibodies to achieve rapid detection within 5 min. The platform demonstrates a low detection limit of 0.05 ng/mL, with a broad dynamic range from 0.1 ng/mL to 25.6 ng/mL. Reproducibility tests confirm consistent performance, with both inter- and intra-assay variation remaining under a 20% coefficient of variation (%CV). Comparative evaluation with standard benchtop systems underscores its accuracy and field applicability. This portable and user-friendly device provides a powerful tool for real-time mycotoxin monitoring, offering significant potential for improving food safety practices and enabling point-of-need testing in resource-limited settings.